France's Africa policy at a turning point - Denis Michael Tull (Stiftung Wissenschaft und Politik (SWP), 2005)
In view of the political fiasco of its military intervention in the Ivory Coast (Operation Licorne), France has announced a restructuring of its security policy in sub-Saharan Africa. Following the stalled reforms in French Africa policy introduced in the 1990s this is probably the most important break in the special relationship between Paris and its African 'backyard' (Pré Carré). France is scaling back its involvement in Africa, giving up on unilateral interventions and striving for a gradual multilateralization of its Africa policy. It is to be expected that Paris will take the initiative in promoting a European policy towards Africa that will provide its own policy broader legitimation. (SWP Comments / SWP)
Keywords: 320